2017
DOI: 10.15694/mep.2017.000116
|View full text |Cite
|
Sign up to set email alerts
|

The exam performance of medical students with dyslexia: a review of the literature

Abstract: Introduction:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…As health services internationally seek to expand the diversity of their medical workforce, increasing numbers of doctors are recognised as having specific learning differences (SpLDs) such as dyslexia . In line with this, candidates, educators and regulators all seek to ensure that examinations assessing the competence of doctors, particularly high‐stakes assessments taken towards the end of lengthy and costly medical and specialty training, are fair to all candidates, including those with dyslexia …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As health services internationally seek to expand the diversity of their medical workforce, increasing numbers of doctors are recognised as having specific learning differences (SpLDs) such as dyslexia . In line with this, candidates, educators and regulators all seek to ensure that examinations assessing the competence of doctors, particularly high‐stakes assessments taken towards the end of lengthy and costly medical and specialty training, are fair to all candidates, including those with dyslexia …”
Section: Introductionmentioning
confidence: 99%
“…The two past studies of undergraduate assessment in medical students also explored the performance of students with dyslexia in an objective structured clinical examination (OSCE) . Whereas one found no differences in performance of first‐ or second‐year medical students in a 16‐station OSCE, the other found that students with dyslexia in Years 1, 2 and 3 of undergraduate medical training had lower performance in certain types of OSCE station, including those involving examination skills and data interpretation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But this was at a cost to their experiencing less of a social life than other students. Compensations such as extra time in written exams can help students with dyslexia—as previous research has shown (Gibson & Leinster, ; McKendree & Snowling, ; Ricketts et al, ; Shaw & Anderson, ). But they also mark them out as different from the rest of their peers.…”
Section: Discussionmentioning
confidence: 87%
“…This project began with a review of the literature (Shaw & Anderson, ), the results of which have been summarized here. This was followed by an autoethnographic study (Shaw, Anderson, & Grant, ).…”
Section: Methodsmentioning
confidence: 99%